MAINTENANCE KOMPRESOR SENTRIFUGAL CENTAX CC 700 MX 3HP - Nurbaiti, Nurbaiti; Hoten, Hendri Van; Helmizar, Helmizar; Bismantolo, Putra; Sulistrionio, Sulistriono (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2020)
PT. Pertamina (Persero) Refinery Unit III (RU III) is one of the Refinery Unit Pertamina that it main activity is process crude oil and intermediate product (Alkylfeed, HSDC,slop oil, LOMC, Long residue, Raw PP) into finished product. One of the important tools is Centrifugal Compressor (CENTAX CC 700 MX 3HP). The problem in the compressor is temperature of the fluida is increase but it pressure is decrease.To solve this problem, sandblasting and coating is used in inspection stage. The result from the inspection was compressor had a leak because the O ring was not functioning optimally and the surface was eroded To overcome this matter, coating is done to prevent the compressor surface from corrosion and replacing the O ring according to size.